2015
DOI: 10.1038/sc.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between clinical assessments of sensory function and electrical perceptual thresholds after incomplete chronic cervical spinal cord injury

Abstract: Study Design Prospective experimental. Objectives To compare sensory function as revealed by light touch and pin prick tests of the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) and the electrical perceptual threshold (EPT) exams in individuals with chronic incomplete cervical spinal cord injury (SCI). Setting Pittsburgh, United States. Methods EPT was tested using cutaneous electrical stimulation (0.5 ms pulse width, 3 Hz) in 32 healthy controls and in 17 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
(37 reference statements)
3
17
0
Order By: Relevance
“…The chronic SCI group was defined based on our previous results highlighting that differences in sensory levels detected by the EPT and ISNCSCI sensory examination followed a similar pattern in persons with SCI up to 10 years post-injury. 9 Because in our previous work, two of the individuals with a SCI for more than 10 years showed different responses, the group with extended-chronic SCI included participants with an injury for more than 10 years. Individuals in the chronic and extended-chronic group were tested at The Miami Project to Cure Paralysis.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chronic SCI group was defined based on our previous results highlighting that differences in sensory levels detected by the EPT and ISNCSCI sensory examination followed a similar pattern in persons with SCI up to 10 years post-injury. 9 Because in our previous work, two of the individuals with a SCI for more than 10 years showed different responses, the group with extended-chronic SCI included participants with an injury for more than 10 years. Individuals in the chronic and extended-chronic group were tested at The Miami Project to Cure Paralysis.…”
Section: Subjectsmentioning
confidence: 99%
“…It has been proposed that the electrical perceptual threshold (EPT) examination, which measures the sensory threshold or minimally detectable electrical stimulus intensity applied to the skin, 3 is a sensitive tool to assess sensory function that can complement the ISNCSCI examination after human SCI. [4][5][6][7][8][9] The ISNCSCI and EPT examinations have both been used to assess persons immediately and at well-defined periods after SCI. Using the ISNCSCI, it was found that most sensory and motor recovery occurs within the first months after cervical SCI, [10][11][12] but some sensorimotor recovery was also detected 1-5 years post-SCI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PA) must compensate the impairment to maximise the potential for recovery and reduce risks for secondary complications 15,16 . The PA in programs of rehabilitation show positive effects on cardiovascular parameters 17 , motor and sensory functions 18 , psychosocial factors 19 , well-being, functionality 20 , quality of life and everyday activities 11 . The appropriate prescription of exercise programs is needed to improve health status and overall quality of life 3 .…”
Section: Introductionmentioning
confidence: 99%